Bimodal Stimulation in Children With Bilateral Profound Sensorineural Hearing Loss: A Suitable Intervention Model for Children at the Early Developmental Stage. Issue 10 (December 2020) - Chen, Ying; Huang, Meiping; Li, Bei; Wang, Zhaoyan; Zhang, Zhihua; Jia, Huan; Hu, Lingxiang; Cai, Yun; Li, Yun; Huang, Zhiwu; Wu, Hao
Abstract : Objective: To evaluate the auditory and speech benefit of bimodal stimulation for prelingual deafened cochlear implantation recipients. Study Design: Retrospective and comparative study. Setting: Tertiary referral center. Patients: Fifty-six children with bilateral prelingual profound sensorineural hearing loss were enrolled, including 28 consecutive children with unilateral cochlear implantation (CI group), and 28 consecutive children with bimodal stimulation (BI group) who used an additional hearing aid (HA) in the contralateral ear. Main Outcome Measures: Hearing assessments included the Infant-Toddler Meaningful Auditory Integration Scale (IT-MAIS) and Categories of Auditory Performance (CAP). Speech evaluations included the Meaningful Use of Speech Scale (MUSS), and Speech Intelligibility Rating (SIR). These measurements were evaluated at the first mapping of cochlear implants and 0.5, 1, 3, 6, 12, 18, 24 months after. Data were analyzed by repeated measures analysis. Results: The mean ages of BI and CI groups were similar (17.6 ± 6.87 vs 19.0 ± 8.10 months, p = 0.497). The initial scores for hearing and speech assessments showed no differences between the two groups, apart from IT-MAIS (2.46 ± 0.631 in BI group vs 0.50 ± 0.279 in CI group, p = 0.004). The auditory and speech development over time were different in the two groups as seen in IT-MAIS ( p < 0.001), CAP ( p = 0.029), MUSS ( p < 0.001), and SIR ( p < 0.001). A continuing but stable difference was observed in CAP, MUSS, and SIR at 3, 18, and 12 months after the first mapping, respectively. In addition, the BI group had better IT-MAIS scores at 3 and 6 months compared with the CI group; however, the difference was not significant after 12 months. Conclusion: Bimodal stimulation is beneficial for prelingually deafened CI recipients who have minimal contralateral residual hearing when bilateral CIs are not available. Hearing aid use in the contralateral ear might be recommended for children after unilateral cochlear implantation to facilitate the development of auditory and speech skills.